Embolization of Ruptured Infratentorial Pial AVM in Pregnancy - Kamil Zeleňák; Dušan Šalát; Branislav Kolarovszki; Egon Kurča; Jana Zeleňáková; Naci Koçer (Life, 2023)
A primigravida 22-year-old woman, at a gestation of 23 weeks, experienced bleeding from a pial arteriovenous malformation (AVM) located in the right cerebellum. After interdisciplinary consensus and with the informed consent of the patient and her family, AVM embolization was performed. Complete occlusion of the AVM was achieved by embolization with PHIL (precipitating hydrophobic injectable liquid). The calculated dose in the uterus was less than 1 µSv, which represents a negligible risk of harmful effects on the fetus. She delivered a baby at 37 weeks of gestation by cesarean section without complications. No congenital disorders were diagnosed by standard screening methods until the age of the newborn was two years. The angiography protocol must be optimized to minimize the radiation dose. Adequate shielding protection of the uterus is important. Premature termination of pregnancy is not necessary. Multidisciplinary care of neurologists, neurosurgeons, interventional radiologists, anesthesiologists, neonatologists, and obstetricians is necessary.